European E-Democracy in Practice - Hennen, Leonhard; van Keulen, Ira; Korthagen, Iris; Aichholzer, Georg; Lindner, Ralf; Nielsen, Rasmus Øjvind (Studies in Digital Politics and Governance, 2020)
This open access book explores how digital tools and social media technologies can contribute to better participation and involvement of EU citizens in European politics. By analyzing selected representative e-participation projects at the local, national and European governmental levels, it identifies the preconditions, best practices and shortcomings of e-participation practices in connection with EU decision-making procedures and institutions. The book features case studies on parliamentary monitoring, e-voting practices, and e-publics, and offers recommendations for improving the integration of e-democracy in European politics and governance. Accordingly, it will appeal to scholars as well as practitioners interested in identifying suitable e-participation tools for European institutions and thus helps to reduce the EU’s current democratic deficit. This book is a continuation of the book “Electronic Democracy in Europe” published by Springer.